Using modified schema-based instruction to teach problem-solving to students with autism and language impairments: a single case design study. - Fernández-Cobos, Raúl; Polo-Blanco, Irene (International Journal of Developmental Disabilities, 2026)
This study evaluates the effect of modified schema-based instruction to teach additive group problem-solving abilities to four students (aged between 11 and 16 years) with autism spectrum disorder and language impairments. The intervention was specifically designed to address language difficulties and to promote the participants' independence by implementing a progressive withdrawal of supports. Results from a multiple-probe design across participants showed evidence of a functional relation between the intervention and the improvement of the participants' problem-solving abilities. All four participants improved their performance with respect to baseline. Three of them acquired problem-solving skills in both addition and subtraction problems, with the acquisition of subtraction skills being less evident for one of them. These three participants generalized their abilities in their regular classroom setting, and also to solving two-step addition problems. Two participants were assessed post-intervention, confirming skill maintenance at three and four weeks, respectively.